2015
DOI: 10.1186/1749-7922-10-3
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for a CT driven classification of left colon acute diverticulitis

Abstract: Computed tomography (CT) imaging is the most appropriate diagnostic tool to confirm suspected left colonic diverticulitis. However, the utility of CT imaging goes beyond accurate diagnosis of diverticulitis; the grade of severity on CT imaging may drive treatment planning of patients presenting with acute diverticulitis.The appropriate management of left colon acute diverticulitis remains still debated because of the vast spectrum of clinical presentations and different approaches to treatment proposed. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
81
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 72 publications
0
81
0
6
Order By: Relevance
“…Staging according to WSES classification [2] was requested for all patients undergoing CT scan at admission:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Staging according to WSES classification [2] was requested for all patients undergoing CT scan at admission:…”
Section: Methodsmentioning
confidence: 99%
“…It does include a variety of conditions, ranging from localized diverticular inflammation to fecal peritonitis. It is usually classified in uncomplicated and complicated according to the extension of the infection process to the peritoneum [2].…”
Section: Introductionmentioning
confidence: 99%
“…For each of these stages, clinical characteristics, radiological findings, and treatment modalities are given [14]. More recently, Sartelli et al [15] have proposed a CT-based classification, with suggested management options, to drive decision-making in nonoperative and operative treatment of ACD. Nevertheless, currently, the modified Hinchey classification (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Initial choice of antibiotic regimen should be empirical and therefore partly depends on presumable pathogens involved, as well as local resistance profiles and other risk factors for resistance patterns [29]. Additional CT imaging is advised in patients with persistent signs of intra-abdominal infection after 4–6 days, or in case of recurrent evidence of infection [15]. Although the reported results seem to indicate that nonoperative management is a viable option, even in patients with extraluminal air, a careful case-by-case decision should still be made, with attention to the patient’s clinical state [30, 31].…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, Colonic diverticulosis is a common condition in modern society due to nutritional habits and lifestyle [1]. Treatment of acute diverticulitis varies from conservative treatment to colonic resection according to the severity of the inflammation, which is usually determined with clinical presentation and imaging findings [2]. The disease recurs in about 20% of patients.…”
mentioning
confidence: 99%